Strategi Peningkatan Daya Saing Industri Obat Tradisional (IOT) di Jawa Tengah Tahun 2017 - Isnaeni Diniarti; Sandi Iljanto (Center for Health Policy and Management, 2017)
Background: The growth of Indonesian traditional medicine exports during 2009-2013 period increased by 6.49% per year. In Indonesia, the Traditional Medicine Industry (IOT) is one of the means that play a role in producing and developing traditional medicines are safe, quality and useful. IOT as an industry is driving the national economy. Objective: Analyze the description of the factors that affect the competitiveness of IOT, providing an alternative strategy in improving the competitiveness of IOT. Method: This research is a descriptive study with qualitative analysis method to conduct in-depth interviews, Focus Group Discussion (FGD), tracking documents. Results: factor conditions; demand conditions; related and supporting industries; firm and strategy rivalry, government roles and opportunity factors are linked and mutually supportive. SWOT identification to develop alternative strategies to enhance IOT competitiveness. Conclusion: The competitiveness of IOT is still lacking, lack of support of factor conditions (capital), related and supporting industries, government roles, firm and strategy rivalry. The role of government affects all components. Enhanced coordination of academia, entrepreneurs, government, and society is needed.